Analisis Perilaku Pemberian ASI Ekskslusif Berdasarkan Pendekatan Theory of Planned Behaviour - Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Exclusive breastfeeding is breastfeeding only for babies until they are 6 months old. The national achievement target is 80%, but the achievement of exclusive breastfeeding in the Mokoau Health Center work area in 2015 is 45.18%. The purpose of this study was to analyze the behavior of exclusive breastfeeding with the theory of planned behavior approach. This type of research is qualitative with a theory of planned behavior approach. The research was carried out at the Azatata BTN Housing in the working area of ​​the Mokoau Health Center, Kendari City, the number of respondents was 5 people. The data is processed descriptively and narrated. The results of the study on attitude showed that 100% of respondents agreed to give exclusive breastfeeding, the subjective norm aspect showed that 3 respondents (60%) stated that their husbands did not support it and 4 respondents (80%) their mothers recommended and gave formula milk when the baby was born. Perceived Behavioral Control, from the aspect of resources, 4 respondents (80%) underwent cesarean delivery, from the income aspect, 100% of respondents were able to provide formula milk, 3 respondents (60%) said health workers did not recommend exclusive breastfeeding, for the opportunity 4 respondents (80%) work and on behavior intention 100% intend to give exclusive breastfeeding. The conclusion of this study is that the low behavior of exclusive breastfeeding is caused by a lack of parental support, lack of husband support, lack of support from health workers, history of cesarean delivery and work. Suggestions for Puskesmas need to provide counseling to the husband's family and parents, for the company to provide a special place for breastfeeding mothers and the need for further research on other factors that cause low exclusive breastfeeding